Glyconanoparticles with controlled morphologies and their interactions with a dendritic cell lectin. Issue 41 (7th October 2016) - Yilmaz, Gokhan; Messager, Lea; Gleinich, Anne S.; Mitchell, Daniel A.; Battaglia, Giuseppe; Becer, C. Remzi
Abstract : Well-defined amphiphilic block glycopolymers with equal mannose content have been self-assembled in aqueous solution to form glyconanoparticles with different morphologies. Abstract : Well-defined amphiphilic block glycopolymers with equal mannose content have been self-assembled in aqueous solution to form glyconanoparticles with different morphologies. The size and shape of nanoparticles have significant effects on the interactions with the dendritic cell-specific intercellular adhesion molecule-3-grabbing non-integrin (DC-SIGN; CD209), characterized using a surface plasmon resonance spectrometer (SPR).